Pengaruh Pendidikan Buddhis Terhadap Penguatan Moralitas Pancadharma Siswa Beragama Buddha - Setiawan, Panya Dama; Supartono, Supartono; Mujiyanto, Mujiyanto (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Buddhist education pancadarma aims to guide individuals in practicing morality. This research applies quantitative research methods and focuses on correlational research. In this particular investigation, the main method used to collect data is through the distribution of questionnaires. The results of the study indicate that Buddhist education has a significant relationship with the strengthening of Pancadharma morality in Buddhist students. Linear regression indicates that about 29% of the variance in moral strengthening can be explained by Buddhist education. Statistical tests confirm that Buddhist education significantly enhances Pancadharma morality, with a low level of significance. This study highlights the important role of Buddhist education in shaping moral values in Buddhist students and provides a deep understanding of its relationship in the context of Buddhism.